Nursing students’ perspectives on learning electronic health record documentation in an academic setting and during clinical placement: a qualitative study - Inger Åse Reierson; Randi Garang Mofossbakke; Hilde Solli (BMC Nursing)
Abstract Background Nursing documentation is pivotal for ensuring high-quality nursing care and patient safety. Studies have demonstrated the importance of learning electronic health record documentation in academic settings to prepare nursing students for practice and further training during clinical placement. Training using simulated electronic health records is therefore encouraged. This study aimed to explore bachelor nursing students’ perspectives on learning electronic health record documentation in an academic setting and during their first clinical placement. The study was conducted at a Norwegian university. Methods A qualitative approach with an explorative and descriptive design was chosen. Twenty-one bachelor nursing students participated. All had completed a compulsory academic electronic health record documentation course and their first clinical placement, in a municipality nursing home using the same electronic health record system as in the academic setting. Data were collected via focus groups. A qualitative and reflexive thematic analysis was applied. Results Two main themes were revealed: (1) Basic learning of electronic health record documentation, with the following subthemes: need for sufficient teacher guidance in the academic setting and appreciation of peer learning during group assignment. (2) Experiences and challenges during clinical placement, with the subthemes: appreciation of mentoring whilst in clinical placement, feeling of being ‘on your own’, worrying about patient safety and reflection on the two-sided learning process. Conclusion This study revealed gaps and inaccuracies in the learning of electronic health record documentation during clinical placements. Nursing students emphasized the importance of learning electronic health record documentation in an academic setting as well as having feedback in the clinical learning process. The study suggests improvement in nursing students’ education in electronic health record documentation, especially in clinical settings.